1997
DOI: 10.1029/97jd01106
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring fire activities in the boreal ecosystem

Abstract: Abstract. Forest fire is a major disturbance to the boreal ecosystem and may interact with climate change. Unfortunately, we have relatively little knowledge regarding fire activities in the boreal ecosystem. This study investigates the extent and dynamics of the forest fires occurred in and around the Boreal Ecosystem-Atmosphere Study (BOREAS) region during summer 1994, an active fire season on record. The statistics of fire activities were obtained from advanced very high resolution radiometer (AVHRR) (aboar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…After one full year of regeneration, NIR reflectance and NDVI recovered significantly toward preburn levels. Canada (1998 and1999) Several previous applications using coarse resolution imagery for burned area mapping in the boreal zone have examined postfire decreases in AVHRR's NDVI (Fraser, Li, & Cihlar, 2000;Kasischke & French, 1995;Li et al, 1997;Li, Nadon, Cihlar, & Stocks, 2000). In the preceding section, it was demonstrated that an SWVI provides superior discrimination of burned boreal forest at the end of the fire season than does the NDVI or individual VGT channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After one full year of regeneration, NIR reflectance and NDVI recovered significantly toward preburn levels. Canada (1998 and1999) Several previous applications using coarse resolution imagery for burned area mapping in the boreal zone have examined postfire decreases in AVHRR's NDVI (Fraser, Li, & Cihlar, 2000;Kasischke & French, 1995;Li et al, 1997;Li, Nadon, Cihlar, & Stocks, 2000). In the preceding section, it was demonstrated that an SWVI provides superior discrimination of burned boreal forest at the end of the fire season than does the NDVI or individual VGT channels.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the AVHRR sensor aboard the NOAA series of meteorological satellites has been the most commonly used spaceborne instrument for characterizing the distribution and impact of boreal fires at regional to continental scales. The sensor has been used for identifying active fires (Flannigan & Vonder Haar, 1986;Li, Cihlar, Moreau, Huang, & Lee, 1997;, detecting smoke plumes (Li, Khananian, & Fraser, 2001), mapping the extent of burned areas (Cahoon, Stocks, Levine, Cofer, & Pierson, 1994;Fraser, Li, & Cihlar, 2000;Kasischke & French, 1995;Li, Nadon, Cihlar, & Stocks, 2000), and estimating trace gas emissions (Cahoon et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Satellites such as NOAA, SPOT, and Landsat have been used in the past to map fire location and extent of fire damage using the visible wavelengths (Li et al, 1997;Fuller, 2000). However, recent spaceborne sensors are able to provide near real time data on global fires and physical geographic variables used in predictive fire behavior models.…”
Section: Firementioning
confidence: 99%
“…Hanuta and LaDochy (1989) used a lightning detection network to examine the thunderstorm climatology of Manitoba. In addition, climatologies have been generated for southern Ontario (Crozier et al, 1988), northern Ontario (Flannigan and Wotton, 1991), the southern Great Lakes area (Clodman and Chisholm, 1996), mid-to northern Saskatchewan (Li et al, 1997), and the subalpine and boreal forest regions of Alberta and Saskatchewan (Nash and Johnson, 1996).…”
Section: Introductionmentioning
confidence: 99%